Evolutionary history of the reef fishAnisotremus interruptus(Perciformes: Haemulidae) throughout the Tropical Eastern Pacific - Palmerin-Serrano, Paola Nallely; Tavera, Jose; Espinoza, Eduardo; Angulo, Arturo [UNESP]; Martinez-Gomez, Juan E.; Gonzalez-Acosta, Adrian F.; Dominguez-Dominguez, Omar (Wiley-Blackwell, 2020)
The Tropical Eastern Pacific (TEP) is a dynamic coastal environment characterized by a complex system of oceanic processes and discontinuous rocky habitats. These features, in conjunction with the ecological and physiological characteristics ofAnisotremus interruptus, might limit gene flow and shape the evolutionary history of the species. In this study, we investigate the evolutionary history of the reef fishA. interruptus(and its Atlantic sister speciesA. surinamensis) throughout its range in the TEP, using two mitochondrial (cox1andcytb) and two nuclear markers (S7andRAG1). We found three genetic groups ofA. interruptuswith recent divergence times from the Galapagos Archipelago, Revillagigedo Archipelago, the continental TEP, andA. surinamensisthe sister specie from the Atlantic. The haplotype mtDNA networks showA. surinamensisin a central position with respect to Pacific genetic haplogroups, whereas nDNA networks show mixed haplotypes between the four genetic groups. In the species tree,A. surinamensisappears as the sister species of all the Pacific samples and the Galapagos Archipelago population emerges as a genetically distinctive group. The samples from the Revillagigedo Archipelago also constitute a genetic distinctive group, closely related to the continental samples. Continental individuals do not show significant genetic structure and exhibit a population expansion during the Pleistocene. The sandy gaps of the TEP not appear to act as barriers isolating populations ofA. interruptus, whereas the open sea gap between the oceanic islands and the continental coast do.
Keywords: Galapagos; genetic structure; Isthmus of Panama; oceanic islands; Revillagigedo